Country data on AMR in Kuwait in the context of community-acquired respiratory tract infections: links between antibiotic susceptibility, local and international antibiotic prescribing guidelines, access to medicine and clinical outcome. (6th September 2022) - Torumkuney, Didem; Behbehani, Naser; van Hasselt, James; Hamouda, Mohamed; Keles, Nergis
Abstract: Background: Antimicrobial resistance (AMR) is one of the biggest threats to global public health. Selection of resistant bacteria is driven by inappropriate use of antibiotics, amongst other factors. COVID-19 may have exacerbated AMR due to unnecessary antibiotic prescribing. Country-level knowledge is needed to understand options for action. Objectives: To review AMR in Kuwait and initiatives underway addressing it. Identifying any areas where more information is required will provide a call to action to minimize any further rise in AMR within Kuwait and to improve patient outcomes. Methods: National initiatives to address AMR, antibiotic use and prescribing, and availability of susceptibility data, particularly for the key community-acquired respiratory tract infection (CA-RTI) pathogens Streptococcus pneumoniae and Haemophilus influenzae, were identified. National and international antibiotic prescribing guidelines commonly used locally for specific CA-RTIs (community-acquired pneumonia, acute otitis media and acute bacterial rhinosinusitis) were also reviewed, plus local antibiotic availability. Insights from a clinician in Kuwait were sought to contextualize this information. Conclusions: In Kuwait there have been some initiatives addressing AMR such as annual campaigns for proper use of antibiotics. Antibiotic use is high but there appears to be a low understanding in the general public about their appropriate use. However, there is legislation in place prohibiting over-the-counter purchase of antibiotics. Only international guidelines for CA-RTIs are used. A more standardized inclusive approach in developing local guidelines, using up-to-date surveillance data of isolates from community-acquired infections in Kuwait, could make management guideline use more locally relevant for clinicians. This would pave the way for a higher level of appropriate antibiotic prescribing and improved adherence. This would, in turn, potentially limit AMR development and improve clinical patient outcomes.